Особенности рабочего процесса радиально-осевых гидротурбин на высокие напоры - Потетенко, Олег Васильевич; Крупа, Евгений Сергеевич (НТУ "ХПИ", 2015)
Рассматриваются особенности рабочего процесса высоконапорных радиально-осевых гидротурбин, причины потерь энергии в подводящих органах и в каналах рабочего колеса, а также анализируются современные методы математического моделирования потока. Исследована вихревая структура потока в подводящих органах и в рабочем колесе высоконапорных гидротурбин и причины, влияющие на нестационарность потока. Предложены направления совершенствования проточных частей радиально-осевых гидротурбин.

The article deals with researches of features workflow of high-pressure Francis turbines, the causes of energy loss in the supply elements and channels of runner. Is investigated vortex structure of the flow in the water supply element and in the runner of high-pressure hydraulic turbines and factors influencing the unsteady flow, causing the pressure pulsation and vibration in the end walls defining the flow. Experimental research of the flow in the spiral, the stay blades and the guide apparatus of the turbine revealed the presence of large-scale vortex formation in the meridional section spiral type "vortex pair." Directions of improving the flow of parts Francis turbines that improve their performance and especially efficiency, reliability and durability of the hydraulic unit. The work presents new type of lead organ with the converging nozzle assembly, combined with the stay blades and the guide apparatus.
Features of working process Francis turbines at high discharge heads
Keywords: рабочее колесо; спиральная камера; мощность; потери энергии; КПД; runner; spiral; energy losses; output